Percutaneous radiofrequency selective rhizotomy of Gasser’s node in treatment of trigeminal neuralgia and cluster headache - Eroshkin, O. A.; Garmish, A. R. (Pain medicine, 2017)
Purpose. Treatment improvement in patients with trigeminal neuralgia and cluster headache using percutaneous radiofrequency selective rhizotomy (PRSR) of Gasser’s node. Materials and methods. Results of treatment of 267 patients with trigeminal neuralgia using PRSR between 2011 and 2015 were analyzed; medical history from 1 to 43 years. 4 patients with cluster headache also underwent PRSR; medical history from 2 to 27 years. Prolonged conservative therapy was ineffective, thus surgery was required. Results. After PRSR in 99 % cases pain stopped. To the end of the 1st day after surgery pain relapsed in 3 (1.1 %) patients. Early pain relapse occurred in cases with mild hypalgesia after PRSR in the area of affected trigeminal branch. Вut dysesthesia occurred in severe hypoesthesia, almost analgesia, that needed appropriate correction. PRSR allows to achieve stable pain regression in 75 % of cluster headache cases observed during three years. Conclusions. The advantages of miniinvasive PRSR method in patients with trigeminal neuralgia and cluster headache are bloodless, safety, short-time surgery, use of local anesthesia, no age limits, high efficiency.